2015
DOI: 10.1007/s12011-015-0241-7
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury-Induced Oxidative Stress in Rainbow Trout (Oncorhynchus mykiss) Liver: Ameliorating Effect of Vitamin C

Abstract: The present study was undertaken to evaluate methylmercury-induced alterations in hepatic enzymes and oxidative stress markers in liver tissue of rainbow trout (Oncorhynchus mykiss) by using a perfusion method, and to explore possible protective effect of vitamin C against these alterations. Forty-eight fish were divided into six groups containing control, test, and amelioration groups. The liver of fish in the test groups were exposed to different doses of methylmercury, i.e., 0.6, 1.2, and 2.4 μg L(-1), resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
3
17
1
Order By: Relevance
“…T-GSH and MDA were significantly decreased in PCBexposure groups at 7 days (Table 1). Induction in the levels of MDA in the present study was in agreement with the study performed by Mozhdeganloo et al (2015), which indicated that increased MDA content occurred in rainbow trout (Oncorhynchus mykiss) exposed to methylmercury. All of the antioxidative parameters significantly decreased and increased at 14 and 21 days, respectively, except for T-GSH for the 5 mg/L PCB-exposure groups at 21 days (Table 1).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…T-GSH and MDA were significantly decreased in PCBexposure groups at 7 days (Table 1). Induction in the levels of MDA in the present study was in agreement with the study performed by Mozhdeganloo et al (2015), which indicated that increased MDA content occurred in rainbow trout (Oncorhynchus mykiss) exposed to methylmercury. All of the antioxidative parameters significantly decreased and increased at 14 and 21 days, respectively, except for T-GSH for the 5 mg/L PCB-exposure groups at 21 days (Table 1).…”
Section: Resultssupporting
confidence: 93%
“…All of the antioxidative parameters significantly decreased and increased at 14 and 21 days, respectively, except for T-GSH for the 5 mg/L PCB-exposure groups at 21 days (Table 1). Decreased T-GSH observed at 7 and 14 days was similar to methylmercury-exposed rainbow trout (Mozhdeganloo et al, 2015), whereas the increased T-GSH observed at 21 days (0.5 mg/L) was the same as that following waterborne lead exposure in tilapia (Kaya and Akbulut, 2015). The increased GSH levels in the liver were explained by the enhanced hepatic uptake of amino acid substrates and activity of biosynthetic enzymes leading to the protection of the fish from oxidative damage.…”
Section: Resultsmentioning
confidence: 60%
“…The present study showed that the 48-h LC 50 value of MeHg (28.39 µg L −1 ) to embryos of large yellow croaker was generally lower than fathead minnow (Pimephales promelas, 71 µg L −1 ; Devlin, 2006), killifish (Fundulus heteroclitus, 50 µg L −1 ; Sharp and Neff, 1982), zebrafish (Danio rerio, 90 µg L −1 ; Cambero and Calvo, 2010) and coho salmon (Oncorhynchus kisutch, 54-71 µg L −1 ; Devlin and Mottet, 1992), but higher than the Japanese flounder (Paralichthys olivaceus, 15.3 µg L −1 ; Ren et al, 2019). While the 48-h LC 50 (18.27 µg L −1 ) and 96-h LC 50 (9.28 µg L −1 ) values of MeHg to large yellow croaker larvae was much Frontiers in Marine Science | www.frontiersin.org ;Wobeser, 1975;Mozhdeganloo et al, 2015), blue gourami (Trichogaster trichopterus, 48-h LC 50 , 94 µg L −1 , 96h LC 50 , 89 µg L −1 ; Roales and Perlmutter, 1974) and Japanese flounder (48-h LC 50 , 20.7 µg L −1 , 96-h LC 50 , 16.3 µg L −1 ). Based on these results, large yellow croaker embryos and larvae may be more sensitive to MeHg than most other fish species mentioned above.…”
Section: Acute Toxicity Of Mehg To Embryos and Larvaementioning
confidence: 98%
“…MeHg was reported to affect the growth of various fish species (Mozhdeganloo et al, 2015). The yolk sac is very important to newly hatched larvae as it is the only nutrients source before the larvae open their mouth, and the changes in yolk sac absorption can directly affect the growth of fish embryo-larvae stage (Huang et al, 2010).…”
Section: Toxicity Of Mehg To the Growth And Development Of Embryos Anmentioning
confidence: 99%
“…Although the action of pyrethroids on various target cells is different, oxidative stress (OS), reactive oxygen species (ROS) and reactive nitrogen species (RNS) associated with PER may play critical roles in induction of a variety of toxicities in humans and animals, including neurotoxicity [11] , immunotoxicity [12] , cardiotoxicity [13] , hepatotoxicity [8,10,14,15] , genotoxicity [16] , and cytotoxicity [10,17] . It has been shown that PER induces a significant increase in OS in various types of cells such as erythrocytes, leukocytes, brain cells, heart cells, smooth muscle cells, thymic cells and lymphocytes [2] .…”
Section: Introductionmentioning
confidence: 99%